Cold Compresses on Patient with Fracture: Systematic Review - Rinawati, Rinawati; Harahap, Ali Asman; Alfiansyah, Denni; Nurrahman, Aris; Ritonga, Yuni Santi; Azzam, Rohman (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The purpose of this study was to see whether the cold compress method was effective in overcoming the clinical conditions felt by patients with fractures. This study uses a systematic review approach by collecting several articles from a selected database consisting of ScienceDirect and ProQuest and Pubmed with articles published in 2014-2021. Article searches were conducted by entering the keywords "Ice Compress OR Ice bag AND Pain OR Swelling AND Fracture". Article search was limited to inclusion criteria and exclusion criteria. The inclusion criteria in this study were diabetic patients with fracture. The study design was a randomized controlled trial and a quasi-experimental study, while the exclusion patient trauma non fracture, cross sectional and literature study. The conclusion in this study Cold compresses can be used to treat swelling, edema and pain in patients with fractures but there are other therapies that are more effective and comprehensive